2013
DOI: 10.1007/s00125-013-3100-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acid load and risk of type 2 diabetes: the E3N-EPIC cohort study

Abstract: Aims/hypothesis The objective of this study was to evaluate the prospective relationship between dietary acid load, assessed with both the potential renal acid load (PRAL) and the net endogenous acid production (NEAP) scores, and type 2 diabetes risk. Methods A total of 66,485 women from the E3N-EPIC cohort were followed for incident diabetes over 14 years. PRAL and NEAP scores were derived from nutrient intakes. HRs for type 2 diabetes risk across quartiles of the baseline PRAL and NEAP scores were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
160
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(179 citation statements)
references
References 23 publications
14
160
3
2
Order By: Relevance
“…A previous study showed that an animal-based LCD was associated with all-cause mortality, whereas a LCD based on vegetable sources has a protective effect for all-cause mortality [8]. In this study, intake of carbohydrate to fiber ratio has a positive correlation with PRAL or NEAP, which has been known to be a risk factor for hypertension [24], type 2 diabetes [25, 26], and MetS [27]; and has a negative correlation with fruit and vegetable intake [28, 29], which has a protective effect on human health. On the other hand, the association between carbohydrate intake and this nutrition was not consistent.…”
Section: Discussionmentioning
confidence: 67%
“…A previous study showed that an animal-based LCD was associated with all-cause mortality, whereas a LCD based on vegetable sources has a protective effect for all-cause mortality [8]. In this study, intake of carbohydrate to fiber ratio has a positive correlation with PRAL or NEAP, which has been known to be a risk factor for hypertension [24], type 2 diabetes [25, 26], and MetS [27]; and has a negative correlation with fruit and vegetable intake [28, 29], which has a protective effect on human health. On the other hand, the association between carbohydrate intake and this nutrition was not consistent.…”
Section: Discussionmentioning
confidence: 67%
“…Dietary acid load is estimated by different methods that have been validated in individuals with kidney disease [18]. To date, results have been mixed among the few studies that have assessed the association between dietary acid load and CVD risk factors [8][9][10][11][12]. Although some studies reported a significant adverse association [8][9][10][11], one did not confirm this association [12], or reported different results for either PRAL or Pro:K with cardiometabolic risk factors [8].…”
Section: Discussionmentioning
confidence: 95%
“…To date, results have been mixed among the few studies that have assessed the association between dietary acid load and CVD risk factors [8][9][10][11][12]. Although some studies reported a significant adverse association [8][9][10][11], one did not confirm this association [12], or reported different results for either PRAL or Pro:K with cardiometabolic risk factors [8]. For example, a cross-sectional study of 1136 young women showed a positive and independent association for PRAL (but not Pro:K) with TC and high-density lipoprotein cholesterol, whereas BMI and WC had significant correlation with only Pro:K [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mild metabolic acidosis, measured by plasma lactate, aligns with insulin resistance independent of obesity and is induced by short-term increases in energy and dietary acid load in healthy humans [129]. In large prospective cohort studies, a high dietary acid load was positively associated with T2DM risk and found to be independent of other known risk factors for diabetes [130][131][132]. Meta-analysis of the three prospective cohort studies further confirmed that, after adjustment for other diabetes risk factors, a higher dietary acid load is associated with an increased risk of T2DM [133].…”
Section: Evaluation Of the Antidiabetic Treatments Proposed By Avicennamentioning
confidence: 99%